Asuhan Keperawatan Jiwa pada Ny. N dengan Masalah Utama Risiko Perilaku Kekerasan Akibat Skizofrenia Paranoid di Ruang Arimbi RSJD Dr. Amino Gondohutomo Provinsi Jawa Tengah - Rindi Dwi Aryani; Titi Sri Suyanti; Slamet Wijaya (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Schizophrenia is a chronic mental disorder known for unclear thoughts, strange behavior and unreal sensory experiences that affect a person's thinking, feeling and acting and can make it difficult to distinguish between what is real and what is not. Patients with schizophrenia who experience delusions often feel angry and may be violent towards people they believe have hurt them. Uncontrolled anger in patients with schizophrenia will cause the risk of violent behavior (Auliati & Lubis, 2023; Wulandari et al., 2024).